Intelligent control of medium and high power converters - Bendaoud, Mohamed; Maleh, Yassine, 1987-; Sanjeevikumar, Padmanaban, 1978- (IET energy engineering series ;, 2023)
Power converters are vital for clean power, and so is their control. This book covers recent advances in converter control, comparing control methods for different converters. Chapters present control of DC-DC and AC-DC converters, for example using sliding mode and robust control.